Developing Automated Tracking Welding Robot - Lê Chí Cương; Đặng Thiện Ngôn (Journal of Technical Education Science, 2012)
This paper presents a new method to accurately determine the welding orbit to control welding head for plane welding, together with the basic mechanical structure and the technical movement of welding head. This result will be developed in the next stage to create an intelligent welding robot that can nondestructively identify the weld.